Knowledge management practices for innovation: an audit tool for improvement. (1st January 2000) - Hull, Richard; Coombs, Rod; Peltu, Malcolm
This document presents a practical tool for analysing and improving the various forms of Knowledge Management activity within the Innovation processes of companies. It is addressed principally to those companies with well-developed and sophisticated units for innovation, such as R&D departments. The Audit Tool has been developed from recently published ethnographic case study research into the relationships between Knowledge Management and Innovation, within an evolutionary economics framework, which seeks to understand the potential contribution of Knowledge Management towards altering the path dependency of a firm's innovation activities. This research developed a distinct and specific focus on Knowledge Management Practices - the various activities, processes and systems which are explicitly intended or utilised for creating and processing knowledge. The "KMPs" identified from case studies were categorised using a basic schema of four attributes for any specific KMP: knowledge processing characteristics, knowledge domain, format of the practice, and perceived contribution to unit performance. This categorisation enabled an initial taxonomy of five main groups of "KMPs for Innovation", according to their relation to: R&D Management activities; the mapping of relationships across technological and organisational boundaries; R&D Human Resource management; the management of Intellectual Property; and the management of information and information technology. These are described and illustrated. The main operational element of this Audit Tool is in the form of a questionnaire, which aims to act as both a discovery mechanism and as a prompt to further reflection on the specific Knowledge Management activities within innovation processes. The questionnaire consists of some 80 questions, each in the form of a description of a specific Knowledge Management Practice, these having been derived from the case studies and additional desk research. This is complemented by a format for specifying action plans for improving KMPs for Innovation.